(untitled) (Research, Society and Development, 2024)
Objective: to analyze evidence found in national and international scientific productions about the practice of the healthcare team of adverse reactions from the use of sedation and analgesia in the PICU. Methodology: This is an integrative literature review, with the following search question: What is the health team’s practice regarding adverse reactions from the use of sedation and analgesia in the pediatric population admitted to the PICU? After reading the entire selected articles, thematic analysis according to Minayo was used. Results: The review included 16 studies and, after reading the selected articles, a thematic analysis was carried out, which identified three thematic units, namely: (1) potential risks of prolonged use of sedatives and analgesics; (2) analgesia and sedation management and protocols used by the healthcare team and (3) the context of pain, sedation, and abstinence in professional practice in the PICU. Final considerations: it is necessary to increase the knowledge and continued training of the healthcare team to improve the practice and quality of care. Furthermore, multidisciplinary participation is urgent, removing the concentration of knowledge on this topic from the hands of medical professionals and bringing it to all health professionals, especially nurses.